Impact of Inflation, Forex Reserves, and Exchange Rates on the Composite Stock Price Index of Manufacturing Firms in Indonesia - Syaifullah, Andi Mustika; Fattah, Ilham A. (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
This study aims to analyze the influence of macroeconomic factors, namely inflation, foreign exchange reserves, and exchange rates, on the Composite Stock Price Index (IHSG) in Indonesia. The study utilizes secondary data, including IHSG, inflation rates, foreign exchange reserves, and exchange rate fluctuations on the Indonesia Stock Exchange (IDX), and employs multiple linear regression analysis to assess the relationships among these variables. The research adopts a descriptive quantitative approach to systematically describe and interpret the data. The findings reveal that inflation has a positive and significant impact on IHSG, suggesting that rising inflation can stimulate stock market performance under certain conditions. Likewise, the exchange rate demonstrates a positive correlation with IHSG, indicating that currency appreciation may enhance investor confidence and stock price growth. Furthermore, foreign exchange reserves are positively associated with IHSG, reflecting the stabilizing effect of a strong reserve position on financial markets. These results align with existing financial theories that highlight the interconnectedness of macroeconomic stability and stock market performance. The study provides valuable insights for investors, policymakers, and market analysts regarding the macroeconomic determinants of stock market movements. Future research is encouraged to expand the scope by incorporating additional variables, such as interest rates, monetary policy interventions, and global economic trends, to further enhance the understanding of factors influencing IHSG dynamics.